Ionic Carbazole-Based Water-Soluble Two-Photon Photoinitiator and the Fabrication of Biocompatible 3D Hydrogel Scaffold - Gao, Wen; Chao, Hao; Zheng, Yong-Chao; Zhang, Wei-Cai; Liu, Jie; Jin, Feng; Dong, Xian-Zi; Liu, Yan-Hong; Li, Shu-Jing; Zheng, Mei-Ling (ACS applied materials & interfaces, 2021)
Two-photon polymerization of a three-dimensional (3D) hydrogel structure has been widely applied in biological tissue engineering. For improving the biocompatibility of hydrogel structures, a new kind of ionic carbazole water-soluble photoinitiator was prepared to realize the fabrication of a 3D hydrogel structure in aqueous phase. 3,6-Bis[2-(1-methyl-pyridinium)vinyl]-9-methyl-carbazole diiodide (BMVMC) and cucurbit[7]uril (CB7) have been employed to generate a complex with better water solubility by host-guest interactions. The binding ratio of the complex was demonstrated to be 1:1 through the characterization of isothermal titration calorimetry (ITC). The two-photon absorption (TPA) cross section of the complex increases to 2500 GM compared with the 750 GM of the BMVMC molecule. Then, an aqueous-phase photoresist was obtained using the CB7/BMVMC complex as the photoinitiator and poly(ethylene glycol) diacrylate (PEGda) as the hydrogel monomer. Two-photon fabrication capability in aqueous phase has been studied using the as-prepared photoresist. A low laser threshold of 3.7 mW as well as a high resolution of 180 nm are achieved. Benefiting from the fluorescence properties of the photoinitiator, we can achieve the confocal fluorescence images without any assistance of fluorescent probes. Subsequently, a 3D engineered hydrogel scaffold microstructure was fabricated by the two-photon polymerization technology, whose biocompatibility was demonstrated by culturing the structure with living cells of L929. The BMVMC-CB7 complex and the as-prepared photoresist are demonstrated to have good biocompatibility, which is prospective for further application in tissue engineering.Two-photon polymerization of a three-dimensional (3D) hydrogel structure has been widely applied in biological tissue engineering. For improving the biocompatibility of hydrogel structures, a new kind of ionic carbazole water-soluble photoinitiator was prepared to realize the fabrication of a 3D hydrogel structure in aqueous phase. 3,6-Bis[2-(1-methyl-pyridinium)vinyl]-9-methyl-carbazole diiodide (BMVMC) and cucurbit[7]uril (CB7) have been employed to generate a complex with better water solubility by host-guest interactions. The binding ratio of the complex was demonstrated to be 1:1 through the characterization of isothermal titration calorimetry (ITC). The two-photon absorption (TPA) cross section of the complex increases to 2500 GM compared with the 750 GM of the BMVMC molecule. Then, an aqueous-phase photoresist was obtained using the CB7/BMVMC complex as the photoinitiator and poly(ethylene glycol) diacrylate (PEGda) as the hydrogel monomer. Two-photon fabrication capability in aqueous phase has been studied using the as-prepared photoresist. A low laser threshold of 3.7 mW as well as a high resolution of 180 nm are achieved. Benefiting from the fluorescence properties of the photoinitiator, we can achieve the confocal fluorescence images without any assistance of fluorescent probes. Subsequently, a 3D engineered hydrogel scaffold microstructure was fabricated by the two-photon polymerization technology, whose biocompatibility was demonstrated by culturing the structure with living cells of L929. The BMVMC-CB7 complex and the as-prepared photoresist are demonstrated to have good biocompatibility, which is prospective for further application in tissue engineering.